Slovo the unfinished autobiography of ANC leader Joe Slovo - Slovo, Joe. (Melbourne Ocean Press, 1997)
A revealing and highly entertaining autobiography of one of the key figures of the African National Congress, described as South Africa?s ?most important and most popular, white leader.? As an immigrant from Lithuania, a Jew, a communist, a guerrilla fighter and strategist ? and white ? few public figures in South Africa were as demonized by the apartheid government as Joe Slovo.
Keywords: Slovo, Joe